Synthesis and anti-HIV activity of a new isoxazole containing disubstituted 1, 2, 4-oxadiazoles analogs. (15th February 2022) - Kumar Kushwaha, Prem; Saurabh Srivastava, Kumar; Kumari, Neha; Kumar, Rajan; Mitra, Debashis; Sharon, Ashoke
Graphical abstract: Abstract: Continuing on our antiviral drug discovery research, we intended to diversify our lead anti-HIV-1 inhibitor by non-classical isosteric replacement of amide to 1, 2, 4-oxadiazoles. The resulting molecules isoxazole-1, 2, 4-oxadiazole analogs were synthesized using mild bases in ethanol under microwave irradiation. The anti-HIV potential was checked in human CD4 + reporter cell lines, TZM-bl and CEM-GFP, at the highest non-cytotoxic concentration (HNC), demonstrating that 3-((3-(p-tolyl)isoxazol-5-yl)methyl)-1, 2, 4-oxadiazole and 3-((3-(4-chlorophenyl)isoxazol-5-yl)methyl)-1, 2, 4-oxadiazole inhibit HIV-1 replication significantly and could be considered as a new lead candidate against HIV-1.